To HIIT or not to HIIT? The question pregnant women may be searching for online: a descriptive observational study. (March 2021) - Nagpal, TS; Everest, C; Goudreau, AD; Manicks, M; Adamo, KB
Aims: An increasingly popular exercise modality for women is high-intensity interval training (HIIT). Limited research has assessed HIIT during pregnancy, and as a result, pregnant women may inquire about HIIT on their own through online searches. The purpose of this study was to systematically search and critically evaluate online resources that women may access when inquiring about performing HIIT during pregnancy. Methods: Following previously published methodology, we systematically examined the online search engine Google with the terms 'HIIT' and 'pregnancy'. Using the 2019 Canadian Guideline for Physical Activity throughout Pregnancy as a reference, we identified evidence-based safety recommendations that apply to all prenatal exercise regimes. All selected links were assessed for whether or not they included evidence-based exercise and pregnancy safety recommendations. Descriptive analyses were performed to report the frequency of each construct. Results: Seventy-six links were retrieved, and 33 relevant links were selected for inclusion. The majority of the retrieved links recommended that women should consult a healthcare provider before beginning any exercise programme (67%), and modify the intensity and types of exercises in the active HIIT bout based on general pregnancy-related changes (73%) and individual comfort level (55%). Just under half of the links recommended modifying intensity based on prepregnancy activity level (46%), offered trimester-specific recommendations (42%), and only 12% mentioned contraindications to exercise. Conclusion: Publicly accessible information online on HIIT during pregnancy does not routinely adhere to evidence-based safety recommendations for prenatal exercise. Further research on HIIT during pregnancy and public dissemination of findings is required.